Rapid eye movement sleep deprivation induces vascular endothelial dysfunction in rats: roles of oxidative stress-mediated nitric oxide signalling and vitamin c supplementation - Nawi, Afifah (2024)
Rapid eye movement (REM) sleep deprivation (REMsd) is associated with oxidative stress, the primary factor in the mechanism of endothelial dysfunction. Endothelial dysfunction has been attributed to a reduction in nitric oxide (NO.) bioavailability. To date, the mechanism of endothelial dysfunction in REMsd is poorly understood. This study aimed to evaluate the effects of REMsd on systolic blood pressure (SBP), vascular endothelial function, protein expression of endothelial nitric oxide synthase (eNOS), phosphorylated-AKT (p-AKT) and total AKT, levels of oxidative stress marker and antioxidants, and histopathological changes in the aorta. The beneficial effects of vitamin C were also evaluated. Thirty-five (35) adult male Sprague-Dawley rats were equally divided into 5 groups (n=7): free-moving control rats (FMC), REM sleep-deprived rats for 72-h (72-h REMsd), tank control rats (TC), sleep recovered for 72-h after 72-h of REMsd (SR), and 72-h REMsd pretreated with vitamin C (RVC). In the RVC group, rats were administered vitamin C orally for 4 weeks (100 mg/kg/day) before the study commenced. The inverted flowerpot technique was utilised to develop REMsd and was validated by a significant decrease in body weight gain despite a significant increase in food consumption. The descending thoracic aorta was isolated for in vitro functional study (myograph), measurement of protein expression of eNOS, p-AKT, and total AKT, and measurement of oxidative stress marker malondialdehyde (MDA) and antioxidant markers, including superoxide dismutase (SOD) activity, catalase (CAT), glutathione (GSH), and total antioxidant capacity (TAC). The histopathology of the aorta was evaluated by haematoxylin and eosin (H&E) staining and scanning electron microscope (SEM). The 72-h REMsd group demonstrated a significant increase in SBP compared to other groups. In the in vitro functional study, there was hypercontractility of the aorta and impaired endothelium-dependent vasorelaxation in the 72-h REMsd group. The levels of protein expression of eNOS, p-AKT, and AKT were significantly decreased in the 72-h REMsd group compared to the FMC group. There were significantly increased levels of MDA, and decreased levels of SOD, CAT, GSH, and TAC in the 72-h REMsd group compared to other groups, which produce oxidative stress. In the 72-h REMsd group, H&E staining showed endothelial damage and its underlying structures, while the SEM study further confirmed the damage by the presence of dense fibrin networks. The results in the SR and RVC groups were not significantly different compared to the FMC and TC groups. Thus, it is suggested that REMsd-induced endothelial dysfunction due to decreased NO. availability resulting from the decrease in eNOS protein expression. Oxidative stress-induced lipid peroxidation is responsible for endothelial damage in the 72-h REMsd group, which was evidenced by increased MDA levels. Oxidative stress is suggestive to be the mediator for endothelial dysfunction and damage that also disrupts the phosphatidylinositol 3-kinase (PI3K)/ AKT/eNOS signalling pathway. Sleep recovery reverts the changes following REMsd to the baseline values. Supplementation of vitamin C is beneficial in protecting the endothelium against the adverse effects of REMsd.